Smart intercalation and coordination strategy to construct stable ratiometric fluorescence nanoprobes for the detection of anthrax biomarker. Issue 18 (29th June 2022) - Niu, Xiaoxiao; Wang, Meixiang; Zhang, Mengyu; Cao, Rui; Liu, Zhaodi; Hao, Fuying; Sheng, Liangquan; Xu, Huajie
Abstract : L@Mg-Al-Ln-LDHs (Ln = Tb, Eu) constructed by the intercalation coordination strategy exhibited a strong and stable fluorescence reference signal and achieved reliable ratiometric detection of DPA in complex environments and actual spores. Abstract : In this work, two novel fluorescent nanoprobes for detecting the anthrax biomarker 2, 6-dipicolinic acid (DPA) have been developed based on a well-designed anionic sulphonated naphthalene derivative (L ) by intercalating and coordinating Mg-Al-Ln-LDHs (Ln = Tb, Eu). The nanosensors exhibited good photostability and high reference fluorescence intensity due to a strong coordination interaction between the L and Al 3+ ions of Mg-Al-Ln-LDH layers. Meanwhile, attributed to the antenna action of DPA in triggering the characteristic fluorescence emissions of Tb 3+ and Eu 3+ through energy transfer, the L-anchored Mg-Al-Ln-LDH nanoparticles exhibited high sensitivity and selectivity and remarkably stable ratiometric fluorescent detection of anthrax spore biomarkers in aqueous solutions, serum and actual spores. Benefiting from the intercalation and coordination of L into Mg-Al-Ln-LDHs, the obtained L@Mg-Al-Ln-LDHs can provide a reliable and stable reference signal for the fluorescence ratiometric detection of DPA with a limit of detection (LOD) of 11.6 nM and 3.56 × 10 3 spores per mL. More prominently, combining L@Mg-Al-Ln-LDH-based detection test strips with a smartphone demonstrates a reliable, rapid and simple method for real-time monitoring of anthrax biomarkers.